Characterization of Glcci1 expression in a subpopulation of lateral ganglionic eminence progenitors in the mouse telencephalon. Issue 1 (18th August 2017) - Kohli, Vikram; Nardini, Diana; Ehrman, Lisa A.; Waclaw, Ronald R.
Abstract : Background : The lateral ganglionic eminence (LGE) in the ventral telencephalon is a diverse progenitor domain subdivided by distinct gene expression into a dorsal region (dLGE) that gives rise to olfactory bulb and amygdalar interneurons and a ventral region (vLGE) that gives rise to striatal projection neurons. The homeobox gene, Gsx2, is an enriched marker of the LGE and is expressed in a high dorsal to low ventral gradient in the ventricular zone (VZ) as development proceeds. Aside from Gsx2, markers restricted to the VZ in the dLGE and/or vLGE remain largely unknown.Results : Here, we show that the gene and protein expression of Glucocorticoid‐induced transcript 1 ( Glcci1 ) has a similar dorsal to ventral gradient of expression in the VZ as Gsx2. We found that Glcci1 gene and protein expression are reduced in Gsx2 mutants, and are increased in the cortex after early and late Gsx2 misexpression. Moreover, Glcci1 expressing cells are restricted to a subpopulation of Gsx2 positive cells on the basal side of the VZ and co‐express Ascl1, but not the subventricular zone dLGE marker, Sp8.Conclusions : These findings suggest that Glcci1 is a new marker of a subpopulation of LGE VZ progenitor cells in the Gsx2 lineage. Developmental Dynamics 247:222–228, 2018 . © 2017 Wiley Periodicals, Inc. Key Findings: Glcci1 is expressed in a high dorsal to low ventral gradient in the LGE. Glcci1 is downstream of Gsx2 in the LGE. Glcci1 is expressed on the basal side of the LGE VZ in the Gsx2 lineage.